The hanging girl - Adler-Olsen, Jussi (Adler-Olsen, Jussi. Department Q novel., 2015)
"New York Times and internationally bestselling author Jussi Adler-Olsen returns with the sixth book in his exhilarating Department Q series, featuring Detective Carl Mørck and his enigmatic assistants, Assad and Rose. In the middle of his usual hard-won morning nap in the basement of police headquarters, Carl Mørck, head of Department Q, receives a call from a colleague working on the Danish island of Bornholm. Carl is dismissive when he realizes that a new case is being foisted on him, but a few hours later, he receives some shocking news that leaves his headstrong assistant Rose more furious than usual. Carl has no choice but to lead Department Q into the tragic cold case of a vivacious seventeen-year-old girl who vanished from school, only to be found dead hanging high up in a tree. The investigation will take them from the remote island of Bornholm to a strange sun worshipping cult, where Carl, Assad, Rose, and newcomer Gordon attempt to stop a string of new murders and a skilled manipulator who refuses to let anything--or anyone--get in the way"--